The wide window - Snicket, Lemony (New York HarperCollins, 2000)
Catastrophes and misfortune continue to plague the Baudelaire orphans after they're sent to live with fearful Aunt Josephine who offers little protection against Count Olaf's treachery.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Humorous stories; Orphans -- Juvenile fiction; Brothers and sisters -- Juvenile fiction